Factors associated with positive perceptions of sealant use on permanent molars among Brazilian dentists - Larissa Yumi ITO; Leticia Maíra WAMBIER; Ana Cláudia Rodrigues CHIBINSKI; Manoelito Ferreira SILVA JUNIOR; Denise Stadler WAMBIER (Brazilian Oral Research)
Abstract This study aimed to analyze the factors associated with the perception among Brazilian dentists of the preventive or therapeutic use of sealants on permanent molars. A cross-sectional web-based survey was conducted with Brazilian dentists between July and October 2021 to examine their use of social media and gather data regarding sealant-related practices. A structured questionnaire was developed and applied to collect information on participants’ professional profiles, clinical indications, materials, techniques, and perceptions of pit and fissure sealants. The study outcomes were the positive perception of sealant use as: (a) a preventive measure, or (b) a therapeutic approach to carious lesions. Responses were dichotomized into positive perception (“strongly agree” or “agree”) and negative perception (“neither agree nor disagree,” “disagree” or “strongly disagree”). Independent variables included sociodemographic, educational, professional, and technical characteristics. Multiple logistic regression models were used to analyze associations (p < 0.05). A total of 2,394 dentists participated in the study, 82.5% of whom had a positive perception of sealants for prevention, and 83.1%, for therapeutic purposes. A greater likelihood of positive perception of preventive sealant use was observed among educators, those employed in public health services, dentists who “always” performed sealant application, and those who used resin sealant, glass ionomer cement, or flowable resin. Conversely, professionals working in capital cities had a lower likelihood of a positive perception. Professionals from cities with populations exceeding 500,000 inhabitants, interior areas, or metropolitan regions were less likely to have a positive perception of therapeutic sealant use. However, those who used resin sealants, glass ionomer cement, or flowable resin were more likely to perceive sealants positively. In conclusion, the positive perception of sealant use for prevention was associated with educational, professional, and technical factors, whereas the positive perception of therapeutic use was associated with professional and technical factors.